EXAMINING THE EFFECT OF SERVANT LEADERSHIP BEHAVIOR ON EMPOWERMENT CLIMATE WITH STRUCTURAL EQUATION MODEL - YILMAZ, Rabia (Atlas Journal, 2021)
Managers, who apply a servant leadership style that focuses on protecting interests of employees, meeting their needs, supporting their development and achievement and therefore, serving them, can also increase their positive perceptions about the organization, such as the empowerment climate. Accordingly, in this study, it was aimed to determine the effect of the servant leadership behaviours of managers on the empowerment climate perceptions of the employees.The study has been applied to 183 white-collar employees who are not the senior level managers and work in specific departments of metal industrial organizations within the scope of ISO Second top 500 largest industrial enterprises located in Ankara. Analyses were created with SPSS 18.0 and AMOS 18.0 programs. The findings of the research show that the servant leadership has positive and meaningful relationship with empowerment climate. Also, it was found the partial effect of servant leadership on the empowerment climate. According to the sub-dimensions; it was also found that empowerment, standing back and accountability have positive effect on information sharing. Empowerment, standing back, courage, and stewardship have positive effect on autonomy through boundaries and finally, standing back, accountability and humility have positive effect on team accountability.